Exploring Rosella (Hibiscus sabdariffa L.) Calyx Extracts as Natural Dye and Antioxidants in Lip Cream Product: Formulation and Evaluation - Ariestanti, Donna Maretta; Mun'im, Abdul; Djajadisastra, Joshita; Hutami, Riska Amalia Putri; Fadhila, Redhalfi; James, Richard Johari (Pharmaceutical Sciences and Research, 2023)
Rosella, also known as Hibiscus sabdariffa L., is a plant that contains anthocyanin compounds in its calyx, which are known for their antioxidant properties. These compounds give the plant a captivating red color and can be used as natural dyes. This study aimed to exploit anthocyanins in rosella calyx as natural dyes and antioxidants in lip cream product. The formulations employed extracts from rosella calyx, a viscous extract from maceration in 96% ethanol (F1) and a commercially available powdered rosella extract (F2). Evaluation on the formulations demonstrated that both F1 and F2 effectively maintained the color integrity of the lip cream. Moreover, an irritation test among 10 respondents showed no adverse reactions. Additionally, a hedonic test of 30 respondents revealed uniformity in homogeneity, odor, and spreadability on both formulations. However, a noticeable contrast emerged in color intensity, with F2 exhibiting greater intensity and preference over F1. The rosella calyx extract also demonstrated its antioxidant potential with an IC50 value of 130.11 ± 2.08 µg/ml. The study highlights the utility of rosella calyx extracts as a dual-functioning component in lip cosmetics. The findings indicate the variations in formulation efficacy and color intensity, emphasizing the potential of rosella-derived extracts in developing cosmetics with enhanced aesthetic appeal and functional antioxidant attributes.